2018
DOI: 10.3390/genes9070318
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor ZafA Regulates the Homeostatic and Adaptive Response to Zinc Starvation in Aspergillus fumigatus

Abstract: One of the most important features that enables Aspergillus fumigatus to grow within a susceptible individual and to cause disease is its ability to obtain Zn2+ ions from the extremely zinc-limited environment provided by host tissues. Zinc uptake from this source in A. fumigatus relies on ZIP transporters encoded by the zrfA, zrfB and zrfC genes. The expression of these genes is tightly regulated by the ZafA transcription factor that regulates zinc homeostasis and is essential for A. fumigatus virulence. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 76 publications
4
57
2
Order By: Relevance
“…Similarly, the expression of the zrfA , zrfB and zrfC was up‐regulated, whereas that of zafA , zrfF , zrcA and zrcC was down‐regulated compared to a Δ srbB mutant (Chung et al, ). Unlike all previous studies carried out under zinc‐replete conditions, we have recently shown that expression of hapX , srbA and srbB and that of several genes encoding proteins involved in iron‐uptake and ergosterol biosynthesis was down‐regulated in zinc‐limiting media under iron‐replete conditions (Vicentefranqueira et al, ). In summary, all previous findings strongly suggested the existence of an interconnection between the regulation of iron and zinc homeostasis, which caused us to contemplate how iron availability influences zafA expression and/or modulated ZafA function even under zinc‐replete conditions.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Similarly, the expression of the zrfA , zrfB and zrfC was up‐regulated, whereas that of zafA , zrfF , zrcA and zrcC was down‐regulated compared to a Δ srbB mutant (Chung et al, ). Unlike all previous studies carried out under zinc‐replete conditions, we have recently shown that expression of hapX , srbA and srbB and that of several genes encoding proteins involved in iron‐uptake and ergosterol biosynthesis was down‐regulated in zinc‐limiting media under iron‐replete conditions (Vicentefranqueira et al, ). In summary, all previous findings strongly suggested the existence of an interconnection between the regulation of iron and zinc homeostasis, which caused us to contemplate how iron availability influences zafA expression and/or modulated ZafA function even under zinc‐replete conditions.…”
Section: Discussioncontrasting
confidence: 77%
“…Actually, the expression of genes involved in iron uptake is down‐regulated in A. fumigatus as an adaptive response to growth in zinc‐limiting, iron‐replete media. This is most likely a mechanism to prevent iron toxicity under zinc starvation (Vicentefranqueira et al, ). In contrast, fungal growth in zinc‐replete media (10‐100 μM zinc) is strongly conditioned by iron, such that fungal growth decreases when the Zn:Fe ratio of the media becomes >3.2 due to iron shortage (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations